Chewing Gum for Intestinal Function Recovery after Colorectal Cancer Surgery: A Systematic Review and Meta-Analysis - Binbin Mei; Wenting Wang; Feifei Cui; Zunjia Wen; Meifen Shen (Gastroenterology Research and Practice)
Background. This meta-analysis was performed to assess the efficacy and safety of chewing gum in intestinal function recovery after colorectal cancer surgery. Methods. A systematic search was conducted in PubMed, Embase, Science Direct, and Cochrane library for relevant randomized controlled trials (RCTs) published until April 2017. Summary risk ratios or weighted mean differences with 95% confidence intervals were used for continuous and dichotomous outcomes, respectively. Results. 17 RCTs with a total number of 1845 patients were included. Gum chewing following colorectal cancer surgery significantly reduced the time to first passage of flatus (WMD −0.55; 95% CI −0.94 to −0.16; P=0.006), first bowel movement (WMD −0.60; 95% CI −0.87 to −0.33; P<0.0001), start feeding (WMD −1.32; 95% CI −2.18 to −0.46; P=0.003), and the length of postoperative hospital stay (WMD −0.88; 95% CI −1.59 to −0.17; P=0.01), but no obvious differences were found in postoperative nausea, vomiting, abdominal distention, pneumonia, and mortality, which were consistent with the findings of intention to treat analysis. Conclusions. Chewing gum could accelerate the recovery of intestinal function after colorectal cancer surgery. However, it confers no advantage in postoperative clinical complications. Further large-scale and high-quality RCTs should be conducted to confirm these results.